Imagination in Practice: The Manipulation of Objects in Mixed Reality through Eidetic Variation - Ferro, Floriana (Aesthetica Preprint, 2025)
This paper explores the application of the phenomenological method of eidetic variation, developed by Edmund Husserl, to mixed reality (MR). Initially, MR is defined within the Reality-Virtuality (RV) continuum developed by Milgram and others (1994) and revisited by Skarbez and others (2021). MR objects, situated within this spectrum, are analyzed phenomenologically as both perceptual and imaginative, constituted by a network of relations. The paper then focuses on Husserl’s method of eidetic variation from Experience and Judgement, which involves arbitrary modification of object characteristics to grasp their essence. This method, though rooted in essentialism, is used by content designers in augmented reality (AR) and virtual reality (VR) to create objects and environments. Lastly, the paper suggests that MR reflects the externalization of imagination through digital technologies, proposing an Analogue-Digital (AD) continuum that integrates human bodily experience and MR technology, facilitating imaginative visualization and creation without searching for the essence of objects.